CREATIVITY TRAINING FOR CHILDREN OF INDONESIAN MIGRANT WORKERS IN "BATIK MAKING" ACTIVITIES - Azizah, Siti Nur; Azizah, Roisah; Fadhillah, Maya Putri; Dzahabiyyah, Tania Putri; Syach, Teddy; Arumsari, Putri Ayu; Syada, Nabila Syafira; Salindri, Fany Oksa; Mas, Nadia (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2024)
The development of creativity is significant in the current era because creativity results from new ways of thinking that support the ability to solve problems. Every child has their creativity. The presence of children's creativity brings joy and satisfaction. Efforts to foster creativity in children must be made from an early age. One example is by carrying out community service in the form of creativity training; with this activity can support children's level and ability to express their thoughts and ideas. Creativity training can be combined with arts and culture. One example is batik creativity training. This service activity is specifically aimed at children of Indonesian Immigrant Workers (PMI) in Malaysia who are currently studying at the Nonformal School . Sanggar Bimbingan is an informal school equivalent to an elementary school in Malaysia, intended for Indonesian immigrant' children. This batik creativity training activity is environmentally friendly because it uses natural media that is safe for the surrounding environment.